Communication Dynamics Between First-Year Doctoral Students and Supervisors - Febrianti, Yusnita; Navitas, Prananda; Winaris, Nuning (Jurnal ILMU KOMUNIKASI, 2023)
Building and maintaining a relationship with the supervisor is crucial for a doctoral student to guarantee stable progress. One of the important aspects is owing to both written and spoken communication, for example, in email and direct conversations. This study examines sample communication activitie of three Indonesian doctoral students and their supervisors to unfold the construction of shared values between them. An appraisal system analyses the linguistic mechanism of engagement, attitude, and graduation systems through which power and relationship are built between first-year doctoral students and their supervisors.